Prevalence of sexual violence among infertile women - Sheikhan, zohreh; Ozgoli, giti; Azar, mahyar; Hosseini, farzaneh; Nasiri, malihe; Amirii, saba (Advances in Nursing & Midwifery, 2014)
Abstract Background & Aims: Violence is a global problem. More than 1. 6 millions of people worldwide lose their lives because of violence every year. Also, many others are injured and suffer from physical, sexual, reproductive and mental problems. 10-69 percent of women experience of physical violence and over 30-50 percent of them experience sexual violence. The purpose of this study was to identify the prevalence and the factors associated with sexual violence against infertile women attending to infertility centers in Tehran, Iran. Materials and Methods: In this cross sectional / descriptive study 400 infertile women attending to infertility centers in Tehran were included. The samples of the study were selected by purposive sampling method. A questionnaire was used for data collection. The questionnaire consisted of demographical characteristics of infertile women, demographical characteristics of husband , The questionnaire of sexual violence that has happened in the last 3 months and Questionnaire of general health. To analyze data, descriptive statistics, Spearman test, one way analysis of variance and SPSS 17 software were used. Findings: Age of women was 30. 50±6. 16. Prevalance of sexual violence was 47. 3%. Sexual violence was significantly associated with income, unwanted marriage ,using drugs and opium and evaluation of total physical health of women and ethnicity , smoking and addiction or drug abuse, mental diseases of the husband and threatened to divorce before treatment , general health status and number of sexual intercourse. (P < 0. 05). Conclusion: One of the main purposes of marriage in developing countries is fertility. Infertile women try many methods of infertility treatment, loneliness and harsh treatment of infertility and sexual and marital problems may be the most important predisposing factor for mental disorders and violence. Factors influence the incidence of violence, smoking , use of drug and physical and mental illnesses. Coping strategies , defining marriage goals , knowledge about infertility treatments , women’s empowerment , intimate relationships can help infertile couples and lessen violence. Key words: Sexual violence , Mental health ,Women ,Infertility